A randomized prospective study of desflurane versus isoflurane in minimal flow anesthesia using "equilibration time" as the change-over point to minimal flow - Tanuja Mallik; S Aneja; R Tope; V Muralidhar (Wolters Kluwer Medknow Publications, 2012)
Background: In the administration of minimal flow anesthesia, traditionally a fixed time period of high flow has been used before changing over to minimal flow. However, newer studies have used "equilibration time" of a volatile anesthetic agent as the change-over point. Materials and Methods: A randomized prospective study was conducted on 60 patients, who were divided into two groups of 30 patients each. Two volatile inhalational anesthetic agents were compared. Group I received desflurane (n = 30) and group II isoflurane (n = 30). Both the groups received an initial high flow till equilibration between inspired (Fi) and expired (Fe) agent concentration were achieved, which was defined as Fe/Fi = 0.8. The mean (SD) equilibration time was obtained for both the agent. Then, a drift in end-tidal agent concentration during the minimal flow anesthesia and recovery profile was noted. Results: The mean equilibration time obtained for desflurane and isoflurane were 4.96 ± 1.60 and 16.96 ± 9.64 min (P < 0.001). The drift in end-tidal agent concentration over time was minimal in the desflurane group (P = 0.065). Recovery time was 5.70 ± 2.78 min in the desflurane group and 8.06 ± 31 min in the isoflurane group (P = 0.004). Conclusion: Use of equilibration time of the volatile anesthetic agent as a change-over point, from high flow to minimal flow, can help us use minimal flow anesthesia, in a more efficient way.